Connectivity Benefits Most Woodland Invertebrate Species but Only in Landscapes With Low Woodland Cover - Charles A. Cunningham; Colin M. Beale; Diana E. Bowler; Michael J. O. Pocock; Robin Hutchinson; Piran C. L. White; Merryn Hunt; Lindsay Maskell; Jane K. Hill (Ecology Letters, 2025)
Connectivity is widely assumed to benefit biodiversity, but this has not been extensively quantified across multiple taxa and landscapes. Focusing on the UK, where woodland cover is low (13%), we analysed species occurrence records from citizen science for over 800 broadleaf woodland‐associated invertebrate species from 15 taxonomic groups in relation to woodland cover and connectivity. Overall, increased woodland connectivity positively affects broadleaf‐associated species occurrence (effect of connectivity across species, accounting for positive effect of broadleaf cover). The benefits of connectivity varied considerably by species: 39% of species showed a significant positive effect, while for 3% it was significantly negative. However, the interaction between cover and connectivity revealed that, overall, connectivity benefits are only found in low cover landscapes. Our findings emphasise potential biodiversity benefits from maximising connectivity when increasing woodland cover and highlight the importance of spatial targeting in restoration efforts, especially in landscapes with low woodland cover.